ISLAM NUSANTARA: CULTURAL CONSERVATION AND STRENGTHEN THE NATION KH. LOHOT HASIBUAN POTRAIT - Mohd Haramen, Muhammad Rafi'i, A Yuli Tauvani, Fahmi Rohim, (The Islamic Education and Multiculturalism Foundation, 2020)
Abstract: This article started from the dynamics of Islam Nusantara that always experience interpretation and contextualization. Various views enrich the idea Islam Nusantara; however various offers to reexamine the idea on Islam Nusantara are inevitable. Taking in-depth interview, this article attempts to explain Kh. Lohot Hasibuan’s views that related to the Islam Nusantara: cultural conservation and it can be also strengthen the nation. In addition, to support this article the data also taking from the document written by Kh. Lohot Hasibuan. To sum up, Islam Nusantara was initiated by Nahdatul Ulama at the congress of 2015 got some polemics, nevertheless various offers contained in the idea of Islam Nusatara, such as accommodating culture, costumes in diversity, he gave the example of Islam occurred in Jambi has same Islamic expression as in Java.